A Study of Manipulation in Some Selected Reports - ' Jawad Almagsosi , Alia; H. Alghezzy , Khalida (Journal of College of Education, 2021)
The current study is concerned with Manipulation as one of the important linguistic phenomena. Manipulation is a linguistic term with great creative potential that is first and foremost topical in the framework of the theory of linguistic manipulation. The widespread and blurry semantic filed of ‘manipulation’ includes the key elements like the speaker’s negative and covert intention that is not evident for the listener. The study aims at showing the concept of manipulation, its types and the use of manipulation in two reports concerning Golan Heights presented by CNN and RT. The study adopts an eclectic model of analysis, Malyuga and et al, 2018, Issers, 2008 and Leontive, 1999 . The study concludes that manipulation is divided into five main types according to: the nature of subject-object interaction, awareness of verbal actions, the type of speech acts, nature of recipient’s response in addition to the objective focus of manipulative efforts. There is a great similarity in the use of manipulation and its types in both reports. The only difference between them is in terms of the ‘nature of subject-object interaction’ that CNN uses direct 100% while RT uses direct and indirect manipulation equally 50%.